Energy assessment of e-motorcycles as a clean transport mode for passenger mobility: A case of Ilala District, Dar es Salaam - Shirima, John Stanslaus; Kiiza, Respicius Clemence; Kusekwa, Mashauri Adam (Tanzania Journal of Engineering and Technology, 2023)
Electric motorcycles or e-motorcycles is a clean mode of road transport that present a prominent solution toward decarbonizing cities. Despite of e-motorcycles being cleaner than gasoline ones, at the moment, there is missing information whether it is feasible to replace gasoline motorcycles with e-motorcycles used for business transport purposes. This paper, therefore, presents the results comparing energy usage when using e-motorcycles and when using the gasoline motorcycles. The energy demand for driving passengers using an e-motorcycle in the precarious routes originated from Gongo la Mboto bus stop to Segerea bus stop, Buguruni Malapa, Gerezani bus stop, Kivukoni bus stop, and Buza bus stop has been estimated. In each route, the energy has been estimated in one and four round-trips. The results reveal that the brushless direct current motor (BLDC) rated 2.5 kW is suitable for driving two passengers while consuming about 0.05 kWh/km at 50 km/h for the distance of 36 km. Increase in route length exhibit the uptrend in total energy required (Etotal). The maximum Etotal for one and four round-trips are 2.5 kWh and 10.0 kWh, respectively, for a route of 36 km length. Considering the energy demand of 2.5 kWh for one round-trip of 36 km, a battery pack of 45 Ah 60 V is found suitable to power the e-motorcycle per charge without compromising the design in terms of weight and size. Consequently, this yields to a saving of about 6.4 kWh, which is around 72 % of the energy that could be used by its gasoline counterpart. This means an e-motorcycle of this power rating could save 0.18 kWh/km, equivalent to 0.02 L/km. Moreover, e-motorcycle could cost 24.3 Tsh/km compared to 754.8 Tsh/km for its gasoline counterpart, and save around 97 % of the fuel cost. These results indicate that an e-motorcycle can outperform its gasoline counterpart. These findings play vital roles in designing energy storage systems and charging infrastructure that could offer a reliable service to end-users and assist to accelerate e-motorcycle adoption. Keywords: e-motorcycle, energy demand, energy consumption, energy saving.